Study on Listeriosis Transmission Dynamics including Time Lag and Media-Driven Behavioral Change - Kapil Toor; Kalyan Das (Department of Mathematics, Universitas Negeri Gorontalo, 2026)
Listeriosis is a foodborne disease caused by the bacterium Listeria monocytogenes, posing significant risks to public health due to its high mortality rate among vulnerable populations. This study develops a comprehensive mathematical model to analyze the dynamics of Listeriosis transmission, incorporating human populations, bacterial growth, food contamination, and the influence of media campaigns. The model divides the human population into compartments of unaware susceptible, aware susceptible, infected, and recovered individuals, while also tracking bacterial populations, media campaigns, and uncontaminated and contaminated food supplies. To capture realistic disease progression, the model includes a delay term τ to account for time lags in awareness campaigns and contamination processes. Stability analysis of the disease-free and endemic steady states is performed to identify critical thresholds for disease control. Additionally, the effects of delays on the system's stability and the potential for oscillatory dynamics are investigated. Sensitivity analysis is conducted to determine the influence of key parameters on disease dynamics. The model provides valuable insights into effective strategies for controlling Listeriosis and mitigating its impact on public health.